Light chain proximal tubulopathy with lambda restriction presenting as acute kidney injury - Asha Thomas; Ram Prasad Elumalai; Barathi Gunabooshanam; Subalakshmi Balasubramanian; Jayakumar Matcha (Society of Diabetic Nephropathy Prevention, 2021)
Monoclonal gammopathies can produce a variety of glomerular, tubular, vascular and interstitial lesions. The spectrums of renal lesions produced by these monoclonal gammopathies include AL/AH amyloidosis, light chain cast nephropathy or myeloma kidney and various proximal tubulopathies. Out of these, proximal tubule centered lesions are much less identified and diagnosed and light chain proximal tubulopathy (LCPT) is one among them. In LCPT the excess free light chains (mostly kappa type by immunofluorescence microscopy) in serum are filtered by the glomeruli and are reabsorbed by proximal tubules causing its damage. These monoclonal light chains when sequestered in the proximal tubules can give rise to crystalline and noncrystalline histological variants. Here we present a rare case of noncrystalline variant of LCPT with lambda light chain restriction who presented with renal insufficiency which on later investigations revealed to be multiple myeloma.